Perspectives, Perceptions and Experiences in Postoperative Pain Management in Developing Countries: A Focus Group Study Conducted in Rwanda - Ana P Johnson; Ryan Mahaffey; Rylan Egan; Theogene Twagirumugabe; Joel L Parlow (Pain Research and Management)
BACKGROUND: Access to postoperative acute pain treatment is an important component of perioperative care and is frequently managed by a multidisciplinary team of anesthesiologists, surgeons, pharmacists, technicians and nurses. In some developing countries, treatment modalities are often not performed due to scarce health care resources, knowledge deficiencies and cultural attitudes.